Measurement of population carrying capacity based on a P-S model: A case study of Zhejiang Province - Linyun Zhang; Wei Li; Dalia Štreimikienė (Amfiteatru Economic Journal, 2020)
The implementation of the "second child policy" and the influx of large numbers of people have led to an increase in the population of Zhejiang Province in China, placing pressure on the environment, health care, and education. In this context, this study intends to use the possibility-satisfaction (P-S) model to predict the population carrying capacity of Zhejiang Province from 2020 to 2025. This prediction system comprises economic, social, resource, and environmental systems. The following conclusions are drawn: the maximum population carrying capacity of Zhejiang in 2025 is 62 million. According to the current population development trend, the population of Zhejiang Province in 2025 will still be within the carrying capacity range. The population carrying capacity of the social system is the weakest.
Keywords: C44; J11; J18; O15; 330; population carrying capacity; index system; possibility-satisfaction model